Museum Sebagai Inovasi Destinasi Alternatif Wellness Tourism - Rr Christiana Mayang Anggraeni Stj; Swastono Putro Pirastyo; Fristi Bellia Annishia; Lu’luwatin Rosdiana Aprilia (STIE Pariwisata API Yogyakarta, 2023)
Wellness tourism is a form of tourism activity that is predicted to become a form of tourist travel with high interest in 2023. In line with this, the stigma of wellness tourism that has developed in society tends to lead to resort and spa tourism, which does provide refreshing services. physical and psychological health. The limited ability of the community to access this form of resort and spa tourism has opened a gap to develop a new destination, which can also fulfill physical and psychological refreshments. This research aims to dig deeper into this gap, to find the potential for innovation in using museums as wellness tourism destinations. This research was conducted using a literature study method, using a Literature Review and Meta[1]ethnography approach. This approach was chosen, because it is hoped that the conclusions from this research can become a new idea for innovation in museum attractions in Indonesia. Data collection was carried out by reviewing various previous studies related to museums and wellness tourism. Data processing resulting from the literature review is carried out through a synthesis system, where all previous research results are recorded, classified, and then concluded. The results obtained from this research show that developing museums as an alternative to wellness tourism is very possible. Theoretical principles of wellness tourism that can be applied to museums include wellness being multi-dimensional, wellness being relatively subjective or perceptual, spiritual, physical, and intellectual. The criteria for museums to be able to fulfill the above principles are formulated as 1) the museum must have an area large enough to support tourist walking activities, 2) the museum collection has a cultural and historical background, 3) the exhibition layout is neat and equipped with clear supporting information, and 4) the museum must be calm enough to support the relaxation process.